Zn(II)-Chlorido complexes of phytohormone kinetin and its derivatives modulate expression of inflammatory mediators in THP-1 cells. - Jan Hošek; Radka Novotná; Petr Babula; Ján Vančo; Zdeněk Trávníček (PLoS ONE, 2013)
Kinetin (N6-furfuryladenine) belongs to a group of plant growth hormones involved in cell division, differentiation and other physiological processes. One of the possible ways to obtain biologically active compounds is to complex biologically relevant natural compounds to suitable metal atoms. In this work, two structural groups of Zn(II) complexes [Zn(L(n))2Cl2]·Solv (1-5) and [Zn(HL(n))Cl3] · xL(n) (6-7); n=1-5, Solv=CH3OH for 1 and 2H2O for 2; x =1 for 6 and 2 for 7; involving a phytohormone kinetin and its derivatives (L(n)) were evaluated for their ability to modulate secretion of tumour necrosis factor (TNF)-α, interleukin (IL)-1β and matrix metalloproteinase (MMP)-2 in a lipopolysaccharide (LPS)-activated macrophage-like THP-1 cell model. The penetration of the complexes to cells was also detected. The mechanism of interactions of the zinc(II) complexes with a fluorescent sensor N-(6-methoxy-8-quinolyl)-p-toluene sulphonamide (TSQ) and sulfur-containing biomolecules (l-cysteine and reduced glutathione) was studied by electrospray-ionization mass spectrometry and flow-injection analysis with fluorescence detection. The present study showed that the tested complexes exhibited a low cytotoxic effect on the THP-1 cell line (IC50>40 µM), apart from complex 4, with an IC50=10.9 ± 1.1 µM. Regarding the inflammation-related processes, the Zn(II) complexes significantly decreased IL-1β production by a factor of 1.47-2.22 compared with the control (DMSO), but did not affect TNF-α and MMP-2 secretions. However, application of the Zn(II) complexes noticeably changed the pro-MMP-2/MMP-2 ratio towards a higher amount of maturated MMP-2, when they induced a 4-times higher production of maturated MMP-2 in comparison with the vehicle-treated cells under LPS stimulation. These results indicated that the complexes are able to modulate an inflammatory response by influencing secretion and activity of several inflammation-related cytokines and enzymes.